Dental ontogeny of a white shark embryo. (27th November 2016) - Tomita, Taketeru; Miyamoto, Kei; Kawaguchi, Akira; Toda, Minoru; Oka, Shin‐Ichiro; Nozu, Ryo; Sato, Keiichi
ABSTRACT: Unlike most viviparous vertebrates, lamniform sharks develop functional teeth during early gestation. This feature is considered to be related to their unique reproductive mode where the embryo grows to a large size via feeding on nutritive eggs in utero. However, the developmental process of embryonic teeth is largely uninvestigated. We conducted X‐ray microcomputed tomography to observe the dentitions of early‐, mid‐, and full‐term embryos of the white shark Carcharodon carcharias (Lamniformes, Lamnidae). These data reveal the ontogenetic change of embryonic dentition of the species for the first time. Dentition of the early‐term embryos (∼45 cm precaudal length, PCL) is distinguished from adult dentition by 1) the presence of microscopic teeth in the distalmost region of the paratoquadrate, 2) a fang‐like crown morphology, and 3) a lack of basal concavity of the tooth root. The "intermediate tooth" of early‐term embryos is almost the same size as the adjacent teeth, suggesting that lamnoid‐type heterodonty (lamnoid tooth pattern) has not yet been established. We also discovered that mid‐term embryos (∼80 cm PCL) lack functional dentition. Previous studies have shown that the maternal supply of nutritive eggs in lamnoid sharks ceases during mid‐ to late‐gestation. Thus, discontinuation of functional tooth development is likely associated with the completion of the oophagous (egg‐eating) phase. Replacement teeth in mid‐term embryos include both embryonic and adult‐type teeth, suggesting that the embryo to adult transition in dental morphology occurs during this period. J. Morphol. 278:215–227, 2017. © 2016 Wiley Periodicals, Inc.